2017
DOI: 10.21548/3-2-2380
|View full text |Cite
|
Sign up to set email alerts
|

Grape Maturity and Wine Quality

Abstract: Several indices calculated from grape juice analyses were submitted to statistical analyses in order to determine correlations of these indices with quality of wine made from grapes at different stages of maturity. Curvilinear relationships were obtained enabling an optimum point to be calculated relating grape maturity to maximum wine quality. The application of skin contact in the case of white wine cultivars resulted in earlier maxima for wine quality, thus compensating to an extent for earlier harvesting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
(3 reference statements)
0
15
0
Order By: Relevance
“…Research assessing correlations between fruit composition and fruit quality rated by expert sensory evaluation has determined that sugar:acid ratio is among the best chemical indices for predicting potential wine quality (Du Plessis and Van Rooyen, 1982;Ough and Singleton, 1968). In general, it is suggested that grapes with sugar-to-acid ratios between 30 and 35 can provide the best balance between sugars and acids for table wines (Cox, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Research assessing correlations between fruit composition and fruit quality rated by expert sensory evaluation has determined that sugar:acid ratio is among the best chemical indices for predicting potential wine quality (Du Plessis and Van Rooyen, 1982;Ough and Singleton, 1968). In general, it is suggested that grapes with sugar-to-acid ratios between 30 and 35 can provide the best balance between sugars and acids for table wines (Cox, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Pinotage and Cabernet Sauvignon from the Stellenbosch, Durbanville, Robertson and Elephants River areas (1979 & 1980 vintages) were studied. Sampling at various degrees of maturity ( l 9-290B) and vinification procedures were as described by Du Plessis & Van Rooyen (1982). A total of 128 wines was used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…It was frequently found that single parameters like 0 Balling (OB) or acidity did not give satisfactory results (Berg, 1958;Du Plessis, 1976;Coombe et al, 1980). More recently Du Plessis & Van Rooyen ( 1982) studied curvilinear relationships between several multi-parameter indices and wine quality determined by sensory evaluation, and found promising results for indices like the 0 B/ total titratable acidity (TT A) ratio and the OB.pH product of grape must. In the latter publication, however, no attention was paid to wine composition, especially flavour compounds, in relation to these indices.…”
Section: Introductionmentioning
confidence: 99%
“…Various ripening tools have been developed to determine berry maturity objectively and accurately at harvest. Berry maturity indices include (i) total soluble solids (TSS), (ii) titratable acidity (TA), (iii) pH and (iv) combinations thereof (maturity indexes) (Amerine & Winkler, 1941;Du Plessis & Van Rooyen, 1982;Van Rooyen, 1984;Boulton et al, 1996;Iland et al, 2000;Ribéreau-Gayon et al, 2006;Botes, 2009). Kourakou (1974), Carbonneau et al (1998) and Schneider et al (2002) identified three types of grape maturity levels: (i) technological maturity, which corresponds to maximum sugar accumulation/concentration and low acidity (ii) phenolic maturity, defined as the concentrations of phenolics in the skins and seeds and (iii) aromatic maturity, associated with the decrease in vegetal notes and the evolution of wine volatile profile.…”
Section: Introductionmentioning
confidence: 99%